Gastrointestinal stromal tumor and leiomyoma of the ileum mimicking adnexal mass: A report of two cases - Akman, Levent; Hurşitoğlu, Behiye Seda; Farajov, Rasim; Terek, Mustafa Coşan; Sezak, Murat; Şimşek, Deniz; Yılmaz, Hüseyin (Turkish Journal of Gastroenterology, 2015)
Abstract Adnexal masses are formations seen in women of all ages; they most often include cystic elements. Medical history, physical examination, different imaging methods, and tumor marker determinations must be used together for preoperative evaluation of an adnexal mass. Both benign and malignant tumors of the small intestine are more rarely encountered than malignant tumors of other gastrointestinal system components; although advanced imaging methods and other diagnostic techniques are used, they do not always allow these tumors to be differentiated from adnexal masses. We report here on two cases operated on with the preliminary diagnosis of an adnexal mass, in which the presence of a gastrointestinal stromal tumor and a leiomyoma of the ileum, respectively, was established.